Pretreatment of waste oils with high free fatty acids content for biodiesel production - Mladenović Nataša Đurišić; Zlatica Predojević; Biljana Škrbić (Zaštita Materijala, 2015)
Biodiesel is considered a promising renewable biofuel alternative to petroleum-based diesel fuel, because of its biodegradability and non-toxicity. Generally, it is produced from the vegetable, edible oils obtained from the cultivated crops; the expenses of such raw materials are the major contributor to the cost of biodiesel production resulting in a biofuel that is uncompetitive with diesel. Therefore, low-cost non-edible lipid feedstocks (so-called the 2nd generation feedstocks) have a great potential in competitive and sustainable production of biodiesel. This paper presents a potential of waste oils as raw materials for biodiesel production, explaining the problems of the elevated contents of free fatty acids (FFAs) in such oils in the conventional production process with an alkaline catalyst. Among the methods for pretreatment of feedstocks with high FFAs content, the paper gives a brief overview of the acid pre-esterification, reviewing the studies that have investigated application of sulphuric acid as the most common acid catalyst.